The risks and benefits of using social media to engage consumers in service design and quality improvement in Australian public hospitals: findings from an interview study of key stakeholders - Louisa Walsh; Nerida Hyett; Jayne Howley; Nicole Juniper; Chi Li; Belinda MacLeod-Smith; Sophie Rodier; Sophie J. Hill (BMC, 2021)
Abstract Background Engaging consumers - patients, families, carers and community members who are current or potential service users - in the planning, design, delivery, and improvement of health services is a requirement of public hospital accreditation in Australia. There is evidence of social media being used for consumer engagement in hospitals internationally, but in Australia this use is uncommon and stakeholders' experiences have not been investigated. The aim of the study was to explore the experiences and beliefs of key Australian public hospital stakeholders around using social media as a consumer engagement tool. This article focuses on the study findings relating to methods, risks, and benefits of social media use. Methods Semi-structured interviews were conducted with Australian public hospital stakeholders in consumer representative, consumer engagement/patient experience, communications or quality improvement roles. Qualitative data were analysed using a deductive content analysis method. An advisory committee of consumer and service provider stakeholders provided input into the design and conduct of this study. Results Twenty-six Australian public hospital service providers and consumers were interviewed. Participants described social media being used to: recruit consumers for service design and quality improvement activities; as an online space to conduct consultations or co-design; and, to gather feedback and patient experience data. The risks and benefits discussed by interview participants were grouped into five themes: 1) overcoming barriers to engagement, 2) consumer-initiated engagement; 3) breadth vs depth of engagement, 4) organisational transparency vs control and 5) users causing harm. Conclusions Social media can be used to facilitate consumer engagement in hospital service design and quality improvement. However, social media alone is unlikely to solve broader issues commonly experienced within health consumer engagement activities, such as tokenistic engagement methods, and lack of clear processes for integrating consumer and patient feedback into quality improvement activities.